P143 Projet Jalons: A Provincial Adaptation Of Clinical Practice Guidelines For Depression In Primary Care. (15th August 2013) - Roberge, P; Fournier, L; Brouillet, H
Abstract : Background: The development of a care protocol for major depression in primary care emerged as an extension of a knowledge application programme developed in Quebec (Canada) to improve care for anxiety and depressive disorders in primary care (2012; JALONS: http://www.qualaxia.org/ms/jalons/ ). The main goal of the project was to develop or adapt tools to support primary mental health care providers in their clinical practice. Context: The 2005 reform in Quebec's mental health services aimed at strengthening primary care services, and included the creation of multidisciplinary community-based primary mental healthcare teams. Description of Best Practice: We used the ADAPTE method to develop a care protocol for major depression in primary care tailored for the local context, with a consideration of the organisation of health care services in primary care. The work was monitored by an expert committee composed of mental health specialists, general practitioners, health care administrators and decision-makers at regional and provincial levels. The care protocol is based on two clinical practice guidelines: the NICE guideline on the treatment and management of depression in adults (2010) and the CANMAT clinical guidelines for the management of major depressive disorder in adults (2009). Lessons: We will share the challenges associated with the adaptation of clinical recommendations and organisational strategies to the local context, and the actual implementation of the care protocol in primary care. We will discuss issues dealing with the applicability and successful uptake of recommendations in local contexts (ex.: availability of resources for guideline adaptation, types of professionals involved, barriers).